Mitofusin 2 Is Essential for IP3-Mediated SR/Mitochondria Metabolic Feedback in Ventricular Myocytes - Seidlmayer, Lea K.; Mages, Christine; Berbner, Annette; Eder-Negrin, Petra; Arias-Loza, Paula Anahi; Kaspar, Mathias; Song, Moshi; Dorn, Gerald W.; Kohlhaas, Michael; Frantz, Stefan; Maack, Christoph; Gerull, Brenda; et al. (Frontiers in Physiology, 2019)
Aim: Endothelin-1 (ET-1) and angiotensin II (Ang II) are multifunctional peptide hormones that regulate the function of the cardiovascular and renal systems. Both hormones increase the intracellular production of inositol-1,4,5-trisphosphate (IP3) by activating their membrane-bound receptors. We have previously demonstrated that IP3-mediated sarcoplasmic reticulum (SR) Ca2+ release results in mitochondrial Ca2+ uptake and activation of ATP production. In this study, we tested the hypothesis that intact SR/mitochondria microdomains are required for metabolic IP3-mediated SR/mitochondrial feedback in ventricular myocytes. Methods: As a model for disrupted mitochondrial/SR microdomains, cardio-specific tamoxifen-inducible mitofusin 2 (Mfn2) knock out (KO) mice were used. Mitochondrial Ca2+ uptake, membrane potential, redox state, and ATP generation were monitored in freshly isolated ventricular myocytes from Mfn2 KO mice and their control wild-type (WT) littermates. Results: Stimulation of ET-1 receptors in healthy control myocytes increases mitochondrial Ca2+ uptake, maintains mitochondrial membrane potential and redox balance leading to the enhanced ATP generation. Mitochondrial Ca2+ uptake upon ET-1 stimulation was significantly higher in interfibrillar (IFM) and perinuclear (PNM) mitochondria compared to subsarcolemmal mitochondria (SSM) in WT myocytes. Mfn2 KO completely abolished mitochondrial Ca2+ uptake in IFM and PNM mitochondria but not in SSM. However, mitochondrial Ca2+ uptake induced by beta-adrenergic receptors activation with isoproterenol (ISO) was highest in SSM, intermediate in IFM, and smallest in PNM regions. Furthermore, Mfn2 KO did not affect ISO-induced mitochondrial Ca2+ uptake in SSM and IFM mitochondria; however, enhanced mitochondrial Ca2+ uptake in PNM. In contrast to ET-1, ISO induced a decrease in ATP levels in WT myocytes. Mfn2 KO abolished ATP generation upon ET-1 stimulation but increased ATP levels upon ISO application with highest levels observed in PNM regions. Conclusion: When the physical link between SR and mitochondria by Mfn2 was disrupted, the SR/mitochondrial metabolic feedback mechanism was impaired resulting in the inability of the IP3-mediated SR Ca2+ release to induce ATP production in ventricular myocytes from Mfn2 KO mice. Furthermore, we revealed the difference in Mfn2-mediated SR-mitochondrial communication depending on mitochondrial location and type of communication (IP3R-mRyR1 vs. ryanodine receptor type 2-mitochondrial calcium uniporter).